Molecular cloning, computational analysis and expression pattern of forkhead box l2 (Foxl2) gene in catfish. (October 2016) - Bhat, Irfan Ahmad; Rather, Mohd Ashraf; Dar, Jaffer Yousuf; Sharma, Rupam
Graphical abstract: Highlights: Foxl2 cDNA was cloned from ovary of catfish. The signal peptide analysis predicted C. batrachus Foxl2 as non-secretory protein. Foxl2 protein chiefly interacts with cytochrome P450 protein family. Foxl2 gene was more expressed in ovary, pituitary and brain of female catfish. Abstract: Foxl2 belongs to forkhead/HNF-3-related family of transcription factors which is involved in ovarian differentiation and development. In present study, the Foxl2 mRNA was cloned from ovary of C. batrachus . The full length cDNA sequence of the Foxl2 was 1056 bp which consists of 5′ (41 bp) and 3′ (106 bp) non-coding regions, as well as a 909 bp of open reading frame (ORF) that encodes 302 amino acids. The putative protein was having the theoretical molecular weight (MW) of 34.018 kD and a calculated isoelectric point (pI) of 9.38. There were 11 serine (Ser), 5 threonine (Thr), and 5 tyrosine (Tyr) phosphorylation sites and 2 putative N-glycosylation sites on the predicted protein. The ligand binding sites were predicted to be present on amino acids 42, 49, 50, 91, 92 and 95 respectively. The signal peptide analysis predicted that C. batrachus Foxl2 is a non-secretory protein. The hydropathy profile of Foxl2 protein revealed that this protein is hydrophilic in nature. Protein-protein interaction demonstrated that Foxl2 protein chiefly interacts with cytochrome P450 protein family. The mRNA transcript analysis of various tissues indicated that the C. batrachus Foxl2 mRNA was more expressed in the brain, pituitary and ovary in female while, the former two tissues and testis showed low expression in male. This study provides a basis for further structural and functional exploration of the Foxl2 from C. batrachus, including its deduced protein and its signal transduction function.